UJI AKTIVITAS ANTIBAKTERI SPRAY BAU KAKI EKSTRAK KULIT JERUK NIPIS (Citrus aurantifolia) DENGAN VARIASI Gelling agent TERHADAP BAKTERI Bacillus subtilis - Ade Maria Ulfa; Nofita Nofita; Bangun Saras Sandi (JFL : Jurnal Farmasi Lampung, 2020)
ABSTRACT Sweat is produced by the apocrine glands, if infected by bacteria that play a role in the decay process will certainly produce foot odor. Some of the bacteria that cause, including Staphylococcus epidermis, Corynebacterium acne and there is one bacterium that causes pungent foot odor that is Bacillus subtilis. Bacillus subtilis enzyme leucine dehydrogenase produced the highest, resulting in isovaleric acid foot odor. Lime peel (Citrus aurantifolia) has the potential to be developed for the antibacterial active ingredient of foot odor contained in tannins, alkaloids and flavonoids. Spray can be effective for inhibition of feet due to water fleas or bacterial infections. The purpose of this research is to test the inhibitory zone of the preparation of foot odor spray ethanol extract of lime peel (Citrus aurantifolia) with variations of gelling agent. Bacterial inhibition zone testing on extracts of lime peel spray preparations using the disc method. This test was carried out on spray with extract concentration of 0% extract base carbopol, 0% extract base HPMC, 0.2% extract base carbopol, 0.2% extract base HPMC, 0.4% extract base carbopol, 0.4% extract base HPMC and positive control with an average inhibition zone of 9,13 mm, 9,12 mm, 11,86 mm, 11,29 mm, 13,17 mm, 12,30 mm, 8,13 mm against the bacterium Bacillus subtilis. Antibacterial test results were analyzed using ONE WAY ANOVA, the results of statistical analysis on the preparation of lime peel extract showed a significant inhibition zone difference of 0.000 (P = <0.05) between all concentrations. Lime peel extract spray is effective in inhibiting the bacterium Bacillus subtilis. Key words: Sweat of foot odor, Lime skin (Citrus aurantifolia), Spray, bacteri Bacillus subtilis